Identifying Risk Factors for Appointment No-Shows in a Pediatric Orthopaedic Surgery Clinic: Original Research - Meghan Malloy; Sergey Tarima; Bethany Canales; David Nelson; Jessica Hanley (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Background: Appointment non-adherence in pediatric orthopaedic clinics negatively affects patient outcomes. While previous studies have examined risk factors for missed appointments, there is a lack of such research in pediatric orthopaedics. This study tests the hypothesis that pediatric orthopaedic patients with greater socioeconomic risk are more likely to miss appointments. Our objective is to identify risk factors contributing to missed appointments. Methods: A retrospective chart review was conducted of all visits in an outpatient pediatric orthopaedic clinic and affiliated Midwest level 1 academic hospital in 2019. Possible covariates with appointment attendance collected included sociodemographic information such as age, gender (male/female), race/ethnicity (non-Hispanic White, Black, Hispanic/Latinx, Other), and insurance (Commercial, Medicaid, Medicaid HMO, Other). The main study outcome was appointment status, defined as either “No-Show” or “Attended/Completed.” Using census data, the Area Deprivation Index (ADI) was determined for a matched case (“No-Show”) control sample to quantify socioeconomic risk. Factors associated with appointment non-adherence were analyzed with a logistic regression model. Results: Out of 10,078 total encounters included in the study, there was a no-show rate of 6.61%. Significant predictors of “No-Show” included race (p<0.001), insurance type (p<0.001), and lag days between appointment scheduling and completion (p<0.001). In a matched case-control sub-study, ADI was positively associated with increased odds of “No-Show” (p<0.001), making this model unique from other studies. Conclusions: This data informs pediatric orthopaedic providers of risk factors for appointment non-adherence in order to individualize patient care plans based on specific socioeconomic needs. Efforts to improve appointment adherence may reduce the rate of poor health outcomes and health disparities in underserved areas. Next steps include qualitative assessments to articulate the experience of families who miss appointments to develop a greater standard for more accessible patient-centered care.